LEGAL STANDING PERATURAN SEMA NO. 2 TAHUN 2023 DALAM POLEMIK ATURAN KAWIN BEDA AGAMA: Legal Standing Sema Regulation no. 2 of 2023 in the Polemic on the Rules for Marriage between Different Religions - Masyayih, Ali Akbar; Al Waris, Moh. Wahyu (Constitution Journal, 2024)
Interfaith marriage is currently still a hot topic of discussion among legal observers and the general public. This is very logical considering that Indonesia is a country that is diverse in beliefs, languages ??and religions. The aim of this research is to find out the legal standing or position of SEMA Number 2 of 2023. This research method is normative juridical. The approach used is a statutory regulation approach, namely an approach implemented based on new and/or current legislation in force as related positive law and a concept approach is an approach implemented based on the forms and concepts that can be obtained in opinions. scholarly opinions or legal doctrines relating to related legal issues.  Data collection was carried out by means of literature study. The theory used is Gustav Radbruch's legal certainty. The research results show that SEMA No. 2 of 2023, which was initially hoped to be able to overcome the polemic regarding the regulation of interfaith marriages, however, it is still a long-standing controversy surrounding interfaith marriages. Abstak Perkawinan beda agama pada saat ini masih menjadi perbincangan hangat oleh para pengamat hukum serta khalayak umum. Hal ini sangat logis mengingat Indonesia adalah negara yang beragam dari kepercayaan, Bahasa dan agama. Tujuan penelitian ini yaitu mengetahui legal standing atau kedudukan SEMA Nomor 2 Tahun 2023. Metode penelitian  ini  ialah  yuridis  normatif. Pendekatan   yang   digunakan merupakan    pendekatan    peraturan    perundang-undangan    yakni    pendekatan    yang dilaksanakan  berlandaskan  pada  Peraturan  Perundang-Undangan  baru  dan  atau  sedang berlaku  sebagai  hukum  positif  yang  terkait  dan  pendekatan  konsep  ialah  pendekatan yang  dilaksanakan  dengan  didasarkan  pada  bentuk-bentuk  dan  konsep  yang  dapat diperoleh  dalam  pendapat-pendapat  sarjana  atau  doktrin-doktrin  hukum  yang  berkaitan dengan  persoalan  hukum  terkait.  Pengumpulan  data  dilaksanakan  dengan  cara  studi pustaka. Teori yang digunakan adalah kepastian hukum milik Gustav Radbruch. Hasil penelitian menunjukkan SEMA No. 2 Tahun 2023 yang pada awalnya diharapkan mampu mengatasi polemik peraturan kawin beda agama namun masih saja menjadi polemik kontroversi yang bekepanjanganseputar perkawinan beda agama.